Inhibition of double-stranded RNA-dependent protein kinase prevents oxytosis and ferroptosis in mouse hippocampal HT22 cells. (15th April 2019) - Hirata, Yoko; Iwasaki, Takuya; Makimura, Yukimi; Okajima, Sayaka; Oh-hashi, Kentaro; Takemori, Hiroshi
Highlights: Pharmacological inhibition of PKR alleviate ferroptosis and oxytosis in HT22 cells. The specific PKR inhibitor C16 prevents erastin-induced activation of IRE-JNK pathway. C16 activates the ERK pathway and increases in ATP levels. Abstract: Double-stranded RNA-dependent protein kinase (PKR) is a component of signal transduction pathways mediating various stress signals including oxidative stress and endoplasmic reticulum (ER) stress and is suggested to be implicated in several neurodegenerative diseases. Cell death in neurodegenerative conditions has been linked to oxidative stress; however, the involvement of PKR in endogenous oxidative stress such as oxytosis and ferroptosis which is quite distinct from classical apoptosis remains unknown. We investigated here the effect of a PKR inhibitor C16 (an imidazole-oxindole derivative) on oxytosis and ferroptosis in cultured HT22 mouse hippocampal cells. C16 prevented glutamate- and erastin-induced cell death, reactive oxygen species accumulation, Ca 2+ influx, phosphorylation of inositol-requiring enzyme 1 (IRE1), one of the three branches of ER stress signaling and its downstream signaling components. On the other hand, C16 did not prevent oxidative stress-induced heme oxygenase-1 expression; instead, C16 activated the extracellular signal-regulated kinase pathway. The protective effect of C16 is diminished in PKR knockout HT22 cells. Real time measurements of the oxygen consumption rate and extracellular acidification rate over a long period of time leading to cell death showed that C16 partially prevented erastin-induced mitochondrial and glycolytic dysfunction. These results suggest that PKR is an important component of oxytosis and ferroptosis and the inhibition of PKR is neuroprotective against endogenous oxidative stress-induced cell death and provide an effective strategy for neuroprotection.